Belgische graveurs van heden. (Brussel : Ministerie van Cultuur, 1968)
Minne, Joris ; Masereel, Frans ; Delhez, Victor ; Boonen, Jac ; Roelant, Andre ; Marchoul, Gustave ; Van Ruyssevelt, Jozef ; Cox, Jan ; De Bolle, Francis ; Boon, Marcel ; Verplancke, Pol ; Dille, Frans ; Van Gisbergen, Charles ; Broes, Sep ; Daniels, Albert ; Haccuria, Maurice
boek
Keywords: België